Perceived usefulness, perceived playfulness, perceived price, and rerceived ease of use affecting purchase intention of online music in Malaysia / Rezashah Mohd Salleh, Mohd Hareth Seth and Nur Hidayah Abdullah - Salleh, Rezashah Mohd; Seth, Mohd Hareth; Abdullah, Nur Hidayah (2022)
Music is essential to human culture and daily activities and has existed for many years. The method of consuming music has evolved to suit human needs. Many online music platforms provide this digital music; one of the essential and significant revenues in the world today. This study explains various theoretical and practical ramifications for parties involved in the music business who require understanding of the risk, impact, and opportunities associated with the purchase of online music which is premium services in the Malaysian context. This study explains various theoretical and practical consequences for parties related to the music industry that needs insight into online music's risk, impact, and opportunities in the Malaysian context. The online music industry has evolved quite tremendously. Unfortunately, not much research had been conducted on online music purchases. Therefore, this study aims to examine whether them is a significant positive relationship between 'Perceived Ease of Use', 'Perceived Usefulness', 'Perceived Playfulness' and 'Perceived Price' with customers' 'Purchase Intention' for online music. A conceptual research framework was developed to identify independent variables affecting the Purchase Intention; the dependent variable. Therefore, further action can be strategized to manage the information and benefit concerned parties on consumers' needs to purchase online music. The study also provides opportunities to discuss related issues such as physical music, e-piracy, sustainability and royalties in a broader perspective that directly impact the online music economy.